Reviews and Perspectives on Smart and Sustainable Metropolitan and Regional Cities - Yigitcanlar, Tan (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The notion of smart and sustainable cities offers an integrated and holistic approach to urbanism by aiming to achieve the long-term goals of urban sustainability and resilience. In essence, a smart and sustainable city is an urban locality that functions as a robust system of systems with sustainable practices to generate desired outcomes and futures for all humans and non-humans. This book contributes to improving research and practice in smart and sustainable metropolitan as well as regional cities and urbanism by bringing together literature reviews and scholarly perspective pieces, forming an open access knowledge warehouse. It contains contributions that offer insights into research and practice in smart and sustainable metropolitan and regional cities by producing in-depth conceptual debates and perspectives, insights from the literature and best practice, and thoroughly identified research themes and development trends. This book serves as a repository of relevant information, material, and knowledge to support research, policymaking, practice, and the transferability of experiences to address challenges in establishing smart and sustainable metropolitan as well as regional cities and urbanism in the era of climate change, biodiversity collapse, natural disasters, pandemics, and socioeconomic inequalities.